2017
DOI: 10.1057/s41303-017-0055-0
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ enactment of competing logics in IT governance: polarization, compromise or synthesis?

Abstract: Governing IT while incorporating stakeholders with diverse institutional backgrounds remains a challenge. Stakeholder groups are typically socialized differently and may have different perspectives on IT governance dilemmas. Yet, extant literature offers only limited insight on socialized views on IT governance. This study uses an institutional logics lens to examine how competing institutional logics get connected in IT governance practices through dominant stakeholders' enactment patterns and how these enact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 72 publications
3
57
0
1
Order By: Relevance
“…Second, we further our understanding of the role of professionals in managing competing logics that affect IT innovation. As shown in recent research, different occupational groups influence IT implementations by loosely coupling their practices to multiple logics; ie, they accept elements of a new logic without changing their day-to-day practices (Berente & Yoo, 2012;Boonstra et al, 2017). We demonstrate how actors shift across multiple logics and, thereby, affect IT innovation by managing their hybrid identities.…”
Section: Managing It Innovation Across Multiple Institutional Logicsmentioning
confidence: 58%
See 4 more Smart Citations
“…Second, we further our understanding of the role of professionals in managing competing logics that affect IT innovation. As shown in recent research, different occupational groups influence IT implementations by loosely coupling their practices to multiple logics; ie, they accept elements of a new logic without changing their day-to-day practices (Berente & Yoo, 2012;Boonstra et al, 2017). We demonstrate how actors shift across multiple logics and, thereby, affect IT innovation by managing their hybrid identities.…”
Section: Managing It Innovation Across Multiple Institutional Logicsmentioning
confidence: 58%
“…We add to this body of research by showing how different types of IT innovations can influence the extent to which different institutional logics are either complementary or competing. In addition, we demonstrate the crucial role of professional-managerial hybrids (Waring, 2014) in polarizing or bridging between logics that affect IT innovation (Boonstra et al, 2017) and in determining the strategies of association with and disassociation from IT innovations that threaten the autonomy of professional practice (Jensen, Kjaergaard, & Svejvig, 2009). More specifically, in our case study, we identified three degrees of conflict between institutional logics: "no conflict," "moderate conflict," and "high conflict."…”
Section: Recent Research Suggests That Success Of It Innovations Depementioning
confidence: 84%
See 3 more Smart Citations